1972
DOI: 10.1016/0005-2736(72)90046-6
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the biological properties of polyene antibiotics: Comparison of other polyenes with filipin in their ability to interact specifically with sterol

Abstract: SUMMARYI. The interaction of the five polyene antibiotics filipin, etruscomycin, pimaricin, nystatin and amphotericin B with sterol, primarily free, liposomal and membrane bound cholesterol has been examined. Each of these antibiotics has a characteristic ultraviolet absorption spectrum in aqueous or organic solvents with three or four ultraviolet absorption maxima.Addition of free cholesterol to aqueous solutions of these antibiotics results in a change of the ratio of the ultraviolet absorbance maxima. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
1
1

Year Published

1974
1974
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(114 citation statements)
references
References 30 publications
9
103
1
1
Order By: Relevance
“…antibiotic that binds to unesterified cholesterol and is commonly used in the diagnosis of NPC1 disease (12,16,23). Treatment of NPC1 fibroblasts with either 40 M ␦-T or 80 M ␣-T significantly reduced unesterified cholesterol storage ( Fig.…”
Section: ␦-T Reduces Lysosomal Size and Corrects Ultrastructural Pathmentioning
confidence: 95%
“…antibiotic that binds to unesterified cholesterol and is commonly used in the diagnosis of NPC1 disease (12,16,23). Treatment of NPC1 fibroblasts with either 40 M ␦-T or 80 M ␣-T significantly reduced unesterified cholesterol storage ( Fig.…”
Section: ␦-T Reduces Lysosomal Size and Corrects Ultrastructural Pathmentioning
confidence: 95%
“…Because α-synFL foci represent lipidrich, vesicular clusters blocked in trafficking by α-synFL, we investigated whether these clusters were enriched in sterols by staining with filipin, a fluorescent probe that binds sterols (34). In control cells, filipin displayed canonical staining of the plasma membrane, which has the highest sterol content in the cell (Fig.…”
Section: -Syn4mentioning
confidence: 99%
“…In 1959 Moat, Peters & Srb made the first attempts to use the antifungal effects of polyene antibiotics for selection of auxotrophic mutants in yeast. Polyene antibiotics form complexes with the sterols of cell walls (Lampen, Arnow, Borowska & Laskin, 1962;Norman et al 1972) causing considerable changes in permeability (Lampen et al 1962;Stachiewicz & Quostel, 1963;Kinsky, Luse & van Deenen, 1966). It has also been suggested that polyenes have an effect on the general conformation of the cell wall (Chuen-Chin & Feingold, 1973).…”
Section: Introductionmentioning
confidence: 99%